2015
DOI: 10.3390/nu7010500
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Adrenal Demedullation Lowers Circulating Norepinephrine and Attenuates Growth Restriction but not Reduction of Endocrine Cell Mass in an Ovine Model of Intrauterine Growth Restriction

Abstract: Placental insufficiency is associated with fetal hypoglycemia, hypoxemia, and elevated plasma norepinephrine (NE) that become increasingly pronounced throughout the third trimester and contribute to intrauterine growth restriction (IUGR). This study evaluated the effect of fetal adrenal demedullation (AD) on growth and pancreatic endocrine cell mass. Placental insufficiency-induced IUGR was created by exposing pregnant ewes to elevated ambient temperatures during mid-gestation. Treatment groups consisted of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…This asymmetry was comparable to the ovine endometrial carunclectomy model of placental restriction (De Blasio et al 2006Owens et al 2007bb;Morrison, 2008;Liu et al 2015). We attribute the asymmetric growth in our IUGR lambs to the progressive rise in circulating fetal catecholamines brought on by placental insufficiency-induced hypoxaemia and hypoglycaemia Davis et al 2015). Although not measured in the present study, it is reasonable to assume that our IUGR lambs were exposed to chronically elevated concentrations of catecholamines in utero, as shown previously (Limesand et al 2006.…”
Section: Neonatal Growthsupporting
confidence: 88%
See 1 more Smart Citation
“…This asymmetry was comparable to the ovine endometrial carunclectomy model of placental restriction (De Blasio et al 2006Owens et al 2007bb;Morrison, 2008;Liu et al 2015). We attribute the asymmetric growth in our IUGR lambs to the progressive rise in circulating fetal catecholamines brought on by placental insufficiency-induced hypoxaemia and hypoglycaemia Davis et al 2015). Although not measured in the present study, it is reasonable to assume that our IUGR lambs were exposed to chronically elevated concentrations of catecholamines in utero, as shown previously (Limesand et al 2006.…”
Section: Neonatal Growthsupporting
confidence: 88%
“…Fetuses with placental insufficiency experience progressive nutrient and oxygen deprivation and respond with greater noradrenaline (norepinephrine) and adrenaline (epinephrine) secretion (Greenough et al 1990;Simonetta et al 1997;Danielson et al 2005;. We found that when placental insufficiency was produced by maternal hyperthermia in sheep, the resulting fetal hypercatecholaminaemia inhibited insulin secretion and independently slowed growth (Leos et al 2010;Limesand et al 2013;Macko et al 2013Macko et al , 2016Davis et al 2015). Throughout life, individuals born SGA due to IUGR have less lean mass and reduced muscle strength, which is worsened by slower muscle accretion during infancy (Greenwood et al 1998;Hediger et al 1998;Gale et al 2001;Sayer et al 2004;Kensara et al 2005;Inskip et al 2007;Yliharsila et al 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Conversely, lowering fetal norepinephrine concentrations by adrenal demedullation in a placental insufficiency‐induced model of IUGR resulted in a partial restoration of fetal weight (Davis et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the profound effects of chronically high circulating catecholamines on GSIS in PI‐IUGR fetuses, elevated plasma catecholamines also promote growth restriction and asymmetric growth in PI‐IUGR fetuses, at least in tissues other than the endocrine pancreas (Davis et al . ). Approximately 50% of the growth restriction is associated with chronically elevated plasma catecholamines in PI‐IUGR fetuses because ablation of the adrenal medullae increases fetal weights by this amount despite hypoxaemia and hypoglycaemia.…”
Section: Introductionmentioning
confidence: 97%